FAKTOR-FAKTOR QUALITY OF LIFE WANITA MENJELANG MASA MENOPAUSE DI DESA KALIREJO KEC WAY RATAI KAB PESAWARAN - Oktaviani, Tanti; Fixi Intansari (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
The premenopausal phase is a transitional period experienced by women before entering menopause, marked by various physical, psychological, social, and environmental changes that can affect quality of life. This study aims to identify the factors that influence the quality of life of women approaching menopause in Kalirejo Village, Way Ratai Subdistrict, Pesawaran Regency. The research used a qualitative approach with a phenomenological perspective. The subjects consisted of three women aged 40–45 years who experienced irregular menstrual cycles, were married, lived with their families, and came from lower-middle socioeconomic backgrounds. Data collection techniques included semi-structured interviews, observation, and documentation. The results showed that all subjects experienced a decline in quality of life in aspects of health and functioning, psychological and spiritual well-being, social and economic conditions, and family relationships. Reported complaints included physical fatigue, sleep disturbances, anxiety, mood changes, financial stress, and lack of emotional support from spouses. Imbalances in family relationships and limited environmental comfort also hindered their ability to carry out daily roles. The subjects continued to maintain emotional balance through religious practices, communication with children, and limited involvement in social activities. This study concludes that the quality of life of women approaching menopause is strongly influenced by physical condition, psychological stability, family support, and social and economic circumstances.